British Columbia Children’s Hospital Compass Program: Extending mental health supports for rural Northern communities - Vivian W. L. Tsang; Annie Kim; Tiffany Y. X. Wu; Lynne Hill; Matt Burkey; Megan Crawford; Erica Koopmans; Chantelle Wilson; Roberto Sassi (PLoS ONE, 2026)
Purpose This article evaluates the impact of the Compass Program over the last six years, with a focus on access to mental health services in Northern British Columbia (BC) and Indigenous communities within the region. Methods Compass program data from September 2018 to April 2024 were analyzed. Demographic and clinical characteristics were compared between Northern and other BC regions. Quantitative variables were summarized using descriptive statistics. Findings Northern BC accounts for 21.4% of total Compass encounters. Indigenous youth in this region are particularly underserved, and community providers are more likely to request specialized virtual consultations at Compass than other regions. Anxiety was the most common presenting concern across all regions. Northern BC represented 46% of all Indigenous consultations and showed a steady increase in Indigenous-related calls—from 18% in 2018 to 41% in 2024. Among direct consults in Northern BC, 55% involved Indigenous patients and medication questions were the most common reasons for calling. Conclusions The study highlights the distinct mental health challenges in Northern BC compared to other regions of the province, suggesting the unique socioeconomic and geographical factors contributing to different mental health issues. Further research should be done to explore the impact of specialized child and youth mental health and substance use provider-to-provider consultations in other similarly underserved areas in Canada. The Compass program at BC Children’s Hospital provides a model that tries to navigate mental health disparities of Northern BC, where there is high demand for mental health services. Clinical trials registry number: H23-03251-A001.